Practical aspects of the use of probiotics in pig production: A review - Barba-Vidal, Emili; Martín-Orúe, Susana M.; Castillejos, Lorena (Livestock science, 2019)
•Probiotics are used in all stages: sow herd, nursery and growing-finishing pigs.•Positive aspects of probiotics include: health modulation, performance improvements and technological developments.•Negative aspects of probiotics include: variability, scarce viability, safety and exigent regulations. Probiotics are applied in all the different productive phases of swine production. They are used for multiple purposes, such as improving performance, mitigating diseases, increasing quality of the product or reducing environmental pollutants. Still, their use is not a general tendency in the pig industry. Probiotics are skeptically seen by many nutritionists due to their highly variable results and unpredictable outcomes, when they are used empirically. Recent technological developments, however, have enabled considerable progress in probiotic research in the last few decades. Significant advances have been made in the selection and characterization of specific probiotic cultures, together with the substantiation of claims relating to their use. It therefore seems opportune to conduct a general review concerning the potential role of probiotics in current pig production, analyzing the dimension of their proven effects and providing scientific background to their use. Furthermore, an analysis of strengths, weaknesses, opportunities and threats has been performed in order to assess the prospective role of probiotics in the near future. Many factors can be seen in favor of probiotics, including the capacity to modulate health and improve performance, important technological development and multiple possibilities to enhance their effects. Moreover, they are considered “natural” alternatives to antibiotics and, therefore, are positively supported by customer and legislative pressure. Nevertheless, aspects such as the lack of universal effects, scarce viability in farm conditions, not fully guaranteed safety and exigent regulations have been outlined as the main weak points of probiotics to become fully established in swine production.